Both predation and feeding opportunities may explain changes in survival of Baltic salmon post-smolts - Mäntyniemi, Samu; Romakkaniemi, Atso; Dannewitz, Johan; Palm, Stefan; Pakarinen, Tapani; Pulkkinen, Henni; Gårdmark, Anna; Karlsson, Olle (ICES Journal of Marine Science, 2012)
<qd> Mäntyniemi, S., Romakkaniemi, A., Dannewitz, J., Palm, S., Pakarinen, T., Pulkkinen, H., Gårdmark, A., and Karlsson, O. Both predation and feeding opportunities may explain changes in survival of Baltic salmon post-smolts. – ICES Journal of Marine Science, doi:10.1093/icesjms/fss088. </qd>The survival of wild and hatchery-reared post-smolts of salmon ( Salmo salar ) in the Baltic Sea has declined since the 1990s. Direct observations of the processes affecting survival are, however, lacking. Here, the importance of food availability and predation in regulating post-smolt survival is analysed. Based on previous studies, the following explanatory variables were selected: (i) availability of herring ( Clupea harengus membras ) recruits in the Gulf of Bothnia (Bothnian Sea, Bothnian Bay) in the northern Baltic Sea; (ii) sprat ( Sprattus sprattus balticus ) and herring abundance in the southern Baltic Sea; and (iii) abundance of grey seal ( Halichoerus grypus ) along the post-smolt migration route. Bayesian analysis was used to estimate the relative probability of each of the 32 combinations of these variables and revealed that the model including grey seal abundance and herring recruits per post-smolt had the highest posterior probability and a high coefficient of determination. The results suggest that the declining trend in post-smolt survival is explained by the increased number of grey seals, whereas the annual variation in survival coincides with variation in the recruitment of Bothnian Sea herring. However, it remains uncertain whether the observed correlations arise from direct causalities or other mechanisms.